Topological semimetal porous carbon as a high-performance anode for Li-ion batteries. Issue 23 (30th May 2019) - Xie, Huanhuan; Qie, Yu; Imran, Muhammad; Sun, Qiang
Abstract : Motivated by the advantages of inherent high electronic conductivity and ordered porosity of topological semimetal monoclinic C16 (m-C16 ), we explore its possible use as a lithium-ion battery anode material. Abstract : Motivated by the advantages of inherent high electronic conductivity and ordered porosity of topological semimetal monoclinic C16 (m-C16 ), we explore its possible use as a lithium-ion battery anode material. Using state-of-the-art theoretical calculations, we show that the m-C16 structure has a high specific capacity of 558 mA h g −1, a low Li ion diffusion energy barrier of 0.25 eV, and a small volume change of 3.6% during charging/discharging operation. The overall performance of m-C16 is superior to that of topological semimetal body-centered orthorhombic C16 (bco-C16 ) reported recently with corresponding values of 558 mA h g −1, 0.53 eV and 13.4%. This study further expands the family of porous topological carbon for high-performance anode materials going beyond the commercially used graphite.